Examining Media Ownership and its Effects on Journalism Practices: A Study of Electronic Private Media Houses in Lusaka District of Lusaka Province - Leya Namonje; Sycorax Ndhlovu (Journal of Arts, Humanities and Social Science)
The media in Africa continues to encounter significant obstacles in carrying out its mandate. The continent's little progress in advancing press freedom and freedom of expression has been masked by laws and acts by some regimes that continue to obstruct the establishment of professional and independent media. This study investigates the interplay between media ownership, ethics, and censorship, and their combined influence on the quality of journalism. It highlights the significant role of media ownership in shaping news coverage, with concentrated ownership often leading to biased reporting and a lack of diverse perspectives. The research is guided by the following objectives; to investigate the influence of media ownership in news coverage under private media, to explore the effects of media ethics rating on the quality of journalism under private media, and to assess political bias threats to democracy. The research uses both qualitative and quantitative methods. A sample of 50 respondents is used to collect data. The research found that adherence to ethical principles, such as truthfulness, fairness, and independence, directly correlates with the trustworthiness of journalism. However, the study also revealed significant challenges in this area, particularly the consequences of ethical breaches. Findings emphasize the necessity of a holistic approach to address these challenges, including promoting transparency in media ownership, reinforcing ethical journalism practices, and safeguarding against censorship. The study offers actionable recommendations, such as diversifying media ownership, strengthening legal protections for journalists, enhancing media literacy, and fostering international collaboration to uphold press freedom. By addressing these issues, the African media can evolve into a more independent, ethical, and effective institution, crucial for advancing democracy and informed public discourse.